An Exploratory Analysis on Entrepreneurial Culture and Financial Education Between Students of the Veracruzana University, Veracruz Region - Betancourt, Ignacio Ortiz (European Journal of Economics and Business Studies, 2017)
Entrepreneurial culture and financial education have become two of the most relevant issues on the international agenda, since they are considered as elements in favor of the efficient use of financial resources, as well as they are important for the identification of opportunities which favor the development of self-employment projects, contributing to local economic growth. Nevertheless, Mexican financial authorities note that there is an environment with gaps and deficiencies in terms of financial education, which is more evident among the rural population and sectors of lower education and socioeconomic level, causing inefficient use of resources and a poor culture of financial management, which undoubtedly compromises the stability of most Mexican families. In addition, this lack of financial education has a negative impact on the development of entrepreneurial projects, generating greater economic and social problems, taking into account that entrepreneurship is a mechanism that contributes to the creation of jobs and encourages economic growth. Based on these premises, this study aims to identify the level of entrepreneurial culture and financial education among Universidad Veracruzana students, through a descriptive and exploratory analysis; results shown a high level of entrepreneurial culture and a medium level of financial education but a weak positive correlation among them.